Advocacy, Performance, and Threshold Influences on Decisions to Terminate New Product Development - Green, Stephen G.; Welsh, M. Ann; Dehler, Gordon E. (Academy of Management Journal, 2003)
Termination of new product development projects was examined as an advocacy process influenced by performance judgments and unobserved performance thresholds, and contextual factors related to the radicalness of such projects were studied as influences on those judgments. We applied survival analysis to four panels of data on 80 newly initiated new product development projects. Advocacy, performance judgments, and threshold effects were related to termination decisions. Contextual factors were also related to these processes.